Catalytic Asymmetric Diels–Alder Reaction/[3, 3] Sigmatropic Rearrangement Cascade of 1‐Thiocyanatobutadienes. Issue 29 (19th June 2018) - Zhou, Yuhang; Lin, Lili; Liu, Xiaohua; Hu, Xinyue; Lu, Yan; Zhang, Xiying; Feng, Xiaoming
Abstract: A highly efficient asymmetric Diels–Alder/[3, 3] sigmatropic rearrangement reaction of methyleneindolinones with 1‐thiocyanatobutadienes has been realized by using a chiral N, N ′‐dioxide/nickel(II) complex as the catalyst. A range of cyclohexenyl isothiocyanates were synthesized in high yields with excellent diastereo‐ and enantioselectivities. Based on mechanistic studies, a catalytic cycle with possible transition‐state models were proposed to explain the process. Abstract : ′Nickel′ for your thoughts : A highly efficient asymmetric Diels–Alder/[3, 3] sigmatropic rearrangement reaction of methyleneindolinones with 1‐thiocyanatobutadienes was realized by using a chiral N, N ′‐dioxide/nickel(II) complex as the catalyst. A range of cyclohexenyl isothiocyanates were synthesized in high yields and with excellent diastereo‐ and enantioselectivities. Pg=protecting group.